A Two‐Dimensional Polyimide‐Graphene Heterostructure with Ultra‐fast Interlayer Charge Transfer. Issue 25 (11th May 2021) - Liu, Kejun; Li, Jiang; Qi, Haoyuan; Hambsch, Mike; Rawle, Jonathan; Vázquez, Adrián Romaní; Nia, Ali Shaygan; Pashkin, Alexej; Schneider, Harald; Polozij, Mirosllav; Heine, Thomas; Helm, Manfred; et al.
Abstract: Two‐dimensional polymers (2DPs) are a class of atomically/molecularly thin crystalline organic 2D materials. They are intriguing candidates for the development of unprecedented organic–inorganic 2D van der Waals heterostructures (vdWHs) with exotic physicochemical properties. In this work, we demonstrate the on‐water surface synthesis of large‐area (cm 2 ), monolayer 2D polyimide (2DPI) with 3.1‐nm lattice. Such 2DPI comprises metal‐free porphyrin and perylene units linked by imide bonds. We further achieve a scalable synthesis of 2DPI‐graphene (2DPI‐G) vdWHs via a face‐to‐face co‐assembly of graphene and 2DPI on the water surface. Remarkably, femtosecond transient absorption spectroscopy reveals an ultra‐fast interlayer charge transfer (ca. 60 fs) in the resultant 2DPI‐G vdWH upon protonation by acid, which is equivalent to that of the fastest reports among inorganic 2D vdWHs. Such large interlayer electronic coupling is ascribed to the interlayer cation–π interaction between 2DP and graphene. Abstract : We demonstrate a general but reliable on‐water synthesis and assembly strategy toward the preparation of 2D polyimide (2DPI)‐graphene (G) van der Waals heterostructures (vdWHs) on water surface. Remarkably, femtosecond transient absorption spectroscopy reveals an ultra‐fast interlayer charge transfer (ca. 60 fs) after protonation in the heterostructure, which is among the fastest reports of vdWHs.